PERAN SUMBER DAYA ALAM TERHADAP PEMBANGUNAN EKONOMI BERKELANJUTAN DALAM PERSPEKTIF EKONOMI ISLAM - Damanik, Gita Nurul Fitri (INTERNATIONAL, Journal of Sharia Business Management, 2023)
Natural resources are the foundation for natural capital in development. Therefore, studying the role of natural capital function in decision making for sustainable development is very important. Failure to understand the role of natural capital will lead to suboptimal economic development and will result in social and environmental costs that are detrimental to humans. Natural resources are gifts from Almighty God to mankind. Humans are referred to as Khalifa fil ardh but on the other hand humans also destroy nature. Sustainable development is a development model that respects the balance of nature. Islam gives freedom to exploit many natural resources, especially in Indonesia, but there are limitations, it is also necessary to maintain the balance of nature to conserve natural resources. This study is a literature study. This study discusses the concept of natural resources from the perspective of sustainable economic development from an Islamic point of view.